Study on design formula of shear capacity of RC beams reinforced by CFRP grid with PCM shotcrete method. (1st July 2018) - Guo, Rui; Pan, Yi; Cai, Lianheng; Hino, Shinichi
Highlights: The reinforced effect of CFRP grid-PCM was sufficient. Both vertical and horizontal grids contributed to shear resistance. A design formula based on the concept of effective strain of CFRP grid was proposed. Abstract: The objective of this study was to evaluate the shear capacity of reinforced concrete (RC) beams by using carbon-fiber-reinforced-polymer (CFRP) grid with polymer-cement-mortar (PCM) shotcrete. A new evaluation method of shear capacity based on the concept of effective strain of CFRP grid was proposed by RC beam tests, which were carried out with the reinforced arrangement of CFRP grid as parameters. In order to make this new evaluation method more applicable, we conducted a 3-dimensional finite-element (FE) analysis by incorporating factors such as the influences from shear span ratio of RC beams. Our results suggested that the proposed evaluation method by considering both vertical and horizontal grid was highly effective, and that the share ratios of shear capacity between vertical and horizontal grid presented a nonlinear relationship according to the shear span of RC beams.